Dietary glutamine, glutamic acid and nucleotides increase the carbon turnover (δ 13C) on the intestinal mucosa of weaned piglets - Amorim, A. B. [UNESP]; Berto, D. A. [UNESP]; Saleh, M. A.D. [UNESP]; Miassi, G. M. [UNESP]; Ducatti, C. [UNESP] (Elsevier, 2017)
This study aimed at evaluating the influence of dietary glutamine, glutamic acid and nucleotides on duodenal and jejunal carbon turnover, and on mucosa morphometry of piglets weaned at an age of 21 days. The diets were: Additive-free diet-control (C); 1% of glutamine (G); 1% of glutamic acid (GA); and 1% of nucleotides (N). In intestinal mucosa morphometry trial, 65 animals were used. At day 0 (baseline), five animals were slaughtered to determine the villus height (VH), crypt depth (CD), VH : CD ratio and villi density (VD). The remaining 60 animals were allocated into a randomized block design with 4×3 factorial arrangement (four diets: C-control, G-glutamine, GA-glutamic acid and N-nucleotides; three slaughter ages: 7, 14 and 21 days post-weaning) with five piglets slaughtered per treatment. In carbon turnover trial, 123 animals were used. At day 0 (baseline), three animals were slaughtered to quantify the δ 13C half-life (T50%) and the 99% carbon substitution (T99%) on intestinal mucosa. The remaining 120 animals were blocked by three weight categories (light, medium and heavy) and, randomly assigned to pen with the same four diets from the previous trial with one piglet slaughtered per weight category per treatment at days 1, 2, 4, 5, 7, 9, 13, 20, 27 and 49 after weaning. Morphometric analyses have yielded no consistent results regarding the action of the evaluated additives, and few reproducible age-related effects. The N diets determined lower T50% values (5.18 days) and T99% (17.21 days) than G and C diets (T50%=7.29, 7.58 days and T99%=24.22, 25.17 days, respectively) in the duodenal mucosa. In jejunum, the N, GA and G diets determined the lowest T50% means (4.9, 6.2 and 6.7 days, respectively) and T99% means (15.34, 21.10 and 21.84 days, respectively) in comparison with C diets (T50%=7.44 and T99%=24.72 days). The inclusion of the additives in the diets of piglets accelerated the carbon turnover in piglets during the post-weaning period. The stable isotopes technique (δ 13C) is an important methodology in studies of additives with trophic effects on the intestinal mucosa of the piglets.
Keywords: additives; intestinal epithelium; pigs; stable isotopes